Kinetic model of drying process of pumpkin (Cucurbita moschata duchesne ex poir.) in a convective hot air dryer - Iroemeha C., Onwude Daniel (2016)
Pumpkins are highly perishable and must be preserved properly in order to increase shelf life and enhance carotenoid yield extraction. Convective hot air drying is the most suitable method of pumpkin preservation. The aim of this study was therefore to develop a computer simulation program for the prediction of the drying kinetics of pumpkin (Cucurbita moschata) in a convective hot air dryer. The study investigated the effect of temperature (50, 60, 70 and 80 oC), material thickness (3, 5 and 7 mm) and drying air velocity (0.6 and 1.2 m/s) on the drying kinetics of pumpkin in a convective hot air dryer. Thin-layer drying method was used to obtain experimental data. The experimental data were modelled using empirical and semi-theoretical thin layer drying models. The best fitting model was evaluated based on the coefficient of determination (R2) and sum of square error (SSE). The Hii et al. model, page and two term model showed excellent fit with the experimental data, thus can best describe the drying behaviour of pumpkin. Th experimental data was further used to estimate the effective moisture diffusivities and activation energy of pumpkin by linear regression analysis based on the solutions of Fick's second law of diffusion or its simplified form. The calculated value of moisture diffusivity varied from a minimum of 1.94182 x 10-8 m2/s to a maximum of 9.19583 x 10-8 m2/s, while activation energy varied from 5.02158 kJ/mol to 32.14542 kJ/mol. The results indicated that with increasing temperature, the drying time was reduced. Furthermore, the drying time to reach safe moisture content of <2% increased as the slice thickness increased from 3 mm to 7 mm. Also, the effective moisture diffusivity increased as drying temperature increased and an increase in the slice thickness resulted in a corresponding increase in the activation energy for pumpkin slices. Subsequently, a computer program using MATLAB software was developed (LABUSIMSOFT) to predict the appropriate drying models at different drying conditions. Graphical User Interface (GUI) was created to show the simulation results graphically and also in generating the optimum drying conditions. The results of colour change during the drying process showed that there was a decrease in the three colour parameters (L*, a*, b*) as the drying temperature and time increased. The Chroma value decreased with a corresponding decrease in temperature and drying time during the convective hot air drying of pumpkin. Similarly, the hue angle increased with an increase in drying time. The browning index (BI) increased slightly with an increase in drying time and temperature However, this changes were not significantly different between samples dried at 50 °C and 80 °C at 5% significant level using Tukey HSD. The results of the effect of drying temperature on hardness, cohesiveness, fracturability, springiness, resilience and total carotenoid content (TCC) showed that the drying temperature affected the hardness properties considerably when compared to the control (fresh) sample. Likewise, the cohesiveness and springiness of pumpkin was approximately constant throughout all drying conditions. The total carotenoid content (TCC) of the dried sample was also measured. The results showed that the drying temperature affects the total carotenoid content (TCC) of pumpkin significantly. The TCC reduced as the temperature increased but at a higher temperature of 80 oC, there was a sudden increase in the value of TCC due to a shorter drying time. Overall the study established that, the drying kinetics of pumpkin; depends on drying temperature and material thickness. However, to get the most optimum combination, the developed simulation software (LABUSIMSOFT) rapidly generated the optimum drying conditions of 78 oC drying temperature, 5 mm sample thickness and a drying time PO Of 350 minutes resulting in 3.3X10and drying time during the convective hot air drying of pumpkin. Similarly, the hue angle increased with an increase in drying time. The browning index (BI) increased slightly with an increase in drying time and temperature However, this changes were not significantly different between samples dried at 50 °C and 80 °C at 5% significant level using Tukey HSD. The results of the effect of drying temperature on hardness, cohesiveness, fracturability, springiness, resilience and total carotenoid content (TCC) showed that the drying temperature affected the hardness properties considerably when compared to the control (fresh) sample. Likewise, the cohesiveness and springiness of pumpkin was approximately constant throughout all drying conditions. The total carotenoid content (TCC) of the dried sample was also measured. The results showed that the drying temperature affects the total carotenoid content (TCC) of pumpkin significantly. The TCC reduced as the temperature increased but at a higher temperature of 80 oC, there was a sudden increase in the value of TCC due to a shorter drying time. Overall the study established that, the drying kinetics of pumpkin; depends on drying temperature and material thickness. However, to get the most optimum combination, the developed simulation software (LABUSIMSOFT) rapidly generated the optimum drying conditions of 78 oC drying temperature, 5 mm sample thickness and a drying time of 350 minutes resulting in 3.3χ 10⁻8 m2/s and 24.8347 kJ/mole activation energy. Consequently, the overall colour and textural properties, and total carotenoid content could be retained by using the optimum drying conditions. This study found that the developed computer simulation software has great potential as a simple and yet effective tool for predicting the drying time, optimizing and monitoring the drying process of pumpkin. The results of this study can be applied in the effective design and optimization of industrial convective hot air dryers8 m2/s and 24.8347 kJ/mole activation energy. Consequently, the overall colour and textural properties, and total carotenoid content could be retained by using the optimum drying conditions. This study found that the developed computer simulation software has great potential as a simple and yet effective tool for predicting the drying time, optimizing and monitoring the drying process of pumpkin. The results of this study can be applied in the effective design and optimization of industrial convective hot air dryers